2023
DOI: 10.5194/gmd-16-3927-2023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating precipitation distributions at regional scales: a benchmarking framework and application to CMIP5 and 6 models

Abstract: Abstract. As the resolution of global Earth system models increases, regional-scale evaluations are becoming ever more important. This study presents a framework for quantifying precipitation distributions at regional scales and applies it to evaluate Coupled Model Intercomparison Project (CMIP) 5 and 6 models. We employ the Intergovernmental Panel on Climate Change (IPCC) sixth assessment report (AR6) climate reference regions over land and propose refinements to the oceanic regions based on the homogeneity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…According to the Clausius-Clapeyron relationship, the saturation vapor pressure increases about 7% per K increase in air temperature, and thus this rate is a rough estimate for expected increases in extreme precipitation with climate warming since extreme precipitation tends to happen in saturated atmospheric environments (Allen and Ingram 2002). For TCs, their intensities, precipitation rates, and environmental ocean temperatures are all related (Stansfield and Reed 2021, 2023, Xi et al 2023, which suggests that as climate warming continues TC precipitation rates will increase due to a combination of increasing available atmospheric moisture and increasing TC intensities (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Clausius-Clapeyron relationship, the saturation vapor pressure increases about 7% per K increase in air temperature, and thus this rate is a rough estimate for expected increases in extreme precipitation with climate warming since extreme precipitation tends to happen in saturated atmospheric environments (Allen and Ingram 2002). For TCs, their intensities, precipitation rates, and environmental ocean temperatures are all related (Stansfield and Reed 2021, 2023, Xi et al 2023, which suggests that as climate warming continues TC precipitation rates will increase due to a combination of increasing available atmospheric moisture and increasing TC intensities (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Under global warming, mean precipitation will also contribute to making “wet regions wetter and dry regions dryer” (Held & Soden, 2006; Norris et al., 2019; Trenberth, 2011). Since WD50 is calculated based on annual precipitation, it is strongly correlated with the number of precipitating days and the Simple Daily Intensity Index (Ahn et al., 2023). As such, changes in WD50 went beyond those in R95p and captured various processes affecting mean precipitation (e.g., more frequent wet extremes, longer dry spells, lesser annual precipitation).…”
Section: Discussionmentioning
confidence: 99%
“…Pendergrass and Knutti (2018) captured this unevenness in daily precipitation and found that in many parts of the world, it takes around 12 of the Wettest Days to produce 50% of the precipitation in a year (WD50). Since then, the measure of WD50 has been used in limited instances to characterize precipitation distributions in China (Chen, 2020; Han et al., 2021; Wu et al., 2021) and large‐scale Coupled Model Intercomparison Project 6 (CMIP6) projections (Ahn et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Contributors have helped expand the PMP beyond its traditional large-scale performance summaries of the mean climate (Gleckler et al, 2008). Various evaluation metrics have been implemented to the PMP for climate variability such as El Niño-Southern Oscillation (ENSO) (Planton et al, 2021;Lee et al, 2021a), extratropical modes of variability (Lee et al, 2019(Lee et al, , 2021b, intra-seasonal oscillation (Ahn et al, 2017), monsoons (Sperber and Annamalai, 2014), cloud feedback (Zelinka et al, 2022), and the characteristics of simulated precipitation (Pendergrass et al, 2020;Ahn et al, 2022Ahn et al, , 2023 and extremes (Wehner et al, 2020(Wehner et al, , 2021. This section will provide an overview of each category of the current PMP evaluation metrics with their usage demonstrations.…”
Section: Current Pmp Capabilitiesmentioning
confidence: 99%
“…In some cases, such as for SAM_SON, the models overestimate the observed amplitude. Other authors have used Portrait plots to synthesize CMIP performance of simulated variability (e.g., Sillmann et al, 2013;Bellenger et al, 2014;Cannon 2020;Kim et al, 2020;Planton et al, 2020;Zhang et al, 2021;Ahn et al, 2022Ahn et al, , 2023. The PMP's ETMoV metrics have been used in several model evaluation studies.…”
Section: Extratropical Modes Of Variabilitymentioning
confidence: 99%